The Participation of Society and Students’ Parents in Education Organizing at State 2 Sekayam Senior High School - Heri Priyanto; Aunnurahman Aunnurahman; Aswandi Aswandi (STKIP Singkawang, 2019)
The importance of community and students’ parentsparticipation should be a serious concern for schools because without the support of participation from relevant parties (stakeholders), the quality and objectives of education as desired by all parties will not be easy to realize properly. This research is qualitativeresearch with the type of case study. In this study, a number of data collection techniques will be used, namely participant observation techniques (participant observations), in-depth interviews, and documentation studies. Based on the research that has been done, the following results are obtained (1) School work program to encourage community and students’ parentsparticipation in the implementation of education in Sekayam 2 High School; (2) The forms of community and students’ parentsparticipation in the implementation of education in Sekayam 2 High School are physical and non-physical; (3) The supporting factors for community and students’ parentsparticipation in the implementation of education at Sekayam 2 High School, is the existence of a forum or access to participation, the willingness and ability, hopes of obtaining good and quality education, trust in schools, and positive response from the school; (4) The inhibiting factors of community and students’ parentsparticipation in administering education at State 2 Sekayam Senior High School, are places of residence that are far from school, the economic level is still relatively low, the view that education is the responsibility of the school, the socialization of work programs is not optimal school, and busyness of parents with their work; and (5) The level of community and students’ parentsparticipation in the implementation of education at Sekayam 2 High School, classified as low or passive.